2015
DOI: 10.1038/labinvest.2014.145
|View full text |Cite
|
Sign up to set email alerts
|

A modified murine model of systemic sclerosis: bleomycin given by pump infusion induced skin and pulmonary inflammation and fibrosis

Abstract: Daily subcutaneous (sc) injection of bleomycin (BLM) causes dermal fibrosis but rarely causes lung changes in mice. There are also significant disadvantages to this traditional model for systemic sclerosis, including a variable distribution of lesions and a requirement for repetitive procedures. The present study was undertaken to develop a convenient method of BLM administration that yields stable dermal inflammation and fibrosis with extensive and reproducible interstitial lung disease (ILD) in mice. Osmotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 31 publications
3
44
0
1
Order By: Relevance
“…In the skin, bleomycin can be administered to produce a localized area of cutaneous fibrosis, the most common route of administration being direct subcutaneous injection. Given the difficulty and variability repeated daily injections can pose, however, newer models have emerged using sustained release of bleomycin via subcutaneously implanted osmotic pumps, eliminating the need for daily injections [21,22,26]. This administration method reduces injection site variability and provides a more consistent distribution of lesions in affected skin [22,26].…”
Section: Animal Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the skin, bleomycin can be administered to produce a localized area of cutaneous fibrosis, the most common route of administration being direct subcutaneous injection. Given the difficulty and variability repeated daily injections can pose, however, newer models have emerged using sustained release of bleomycin via subcutaneously implanted osmotic pumps, eliminating the need for daily injections [21,22,26]. This administration method reduces injection site variability and provides a more consistent distribution of lesions in affected skin [22,26].…”
Section: Animal Modelsmentioning
confidence: 99%
“…Many pro-inflammatory cytokines, such as interleukin (IL)-1β, IL-4, IL-6 and CXCL2, are found to be upregulated in the skin of mice injected with bleomycin [21,22]. Additionally, many inflammatory cells, including CD45 + leukocytes, F4/80 + macrophages, CD3 + T lymphocytes and mast cells as well as α-smooth muscle actin (αSMA) positive myofibroblasts, are found in higher numbers in the skin of bleomycin-treated animals versus control [21,22,27]. A downstream effect of this intense inflammatory process is tissue fibrosis and increased collagen deposition.…”
Section: Animal Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…A few reports have shown that systemic delivery of BLM via continuous diffusion from subcutaneously implanted osmotic minipumps can cause fibrosis of the skin, lungs, and other internal organs [10–12]. This approach may provide the opportunity to test the effects of potential therapeutic treatments on fibrosis in each of the affected organs simultaneously.…”
Section: Introductionmentioning
confidence: 99%